2021
DOI: 10.1016/j.ijms.2021.116549
|View full text |Cite
|
Sign up to set email alerts
|

Gas-phase ion/ion chemistry for structurally sensitive probes of gaseous protein ion structure: Electrostatic and electrostatic to covalent cross-linking

Abstract: Intramolecular interactions within a protein are key in maintaining protein tertiary structure and understanding how proteins function. Ion mobility-mass spectrometry (IM-MS) has become a widely used approach in structural biology since it provides rapid measurements of collision cross sections (CCS), which inform on the gas-phase conformation of the biomolecule under study. Gas-phase ion/ion reactions target amino acid residues with specific chemical properties and the modified sites can be identified by MS. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 75 publications
(91 reference statements)
0
30
0
Order By: Relevance
“…Covalent reactions and proton transfer gas-phase ion/ion chemistries between multiply charged cations and “sticky” anionic reagents are known to proceed through the formation of long-lived intermediates stabilized by strong electrostatic interactions. ,,,, Therefore, reaction rates of the covalent modification reactions, observed via neutral loss of the leaving group and proton transfer from the polypeptide to the reagent, can be readily probed by slow-heating methods. , The reagent used for this study was sulfo-benzoyl-HOAt, shown to be favored on kinetic grounds to proton transfer with only a small van der Waals barrier between the nascent covalent product complex and loss of the HOAt leaving group . We have recently used this reagent to probe gas-phase structures of ubiquitin cations formed from aqueous and low-pH methanolic solutions. , Since it is of interest to differentiate between gas-phase structures resulting directly from dehydration of the ions from droplets in the electrospray process and structures produced by activation and refolding of proteins into additional structures (i.e., CIU), the activation enthalpies, entropies, and free energies for the covalent and proton transfer reactions are valuable for characterizing the kinetics and mechanisms of these reactions versus CIU processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Covalent reactions and proton transfer gas-phase ion/ion chemistries between multiply charged cations and “sticky” anionic reagents are known to proceed through the formation of long-lived intermediates stabilized by strong electrostatic interactions. ,,,, Therefore, reaction rates of the covalent modification reactions, observed via neutral loss of the leaving group and proton transfer from the polypeptide to the reagent, can be readily probed by slow-heating methods. , The reagent used for this study was sulfo-benzoyl-HOAt, shown to be favored on kinetic grounds to proton transfer with only a small van der Waals barrier between the nascent covalent product complex and loss of the HOAt leaving group . We have recently used this reagent to probe gas-phase structures of ubiquitin cations formed from aqueous and low-pH methanolic solutions. , Since it is of interest to differentiate between gas-phase structures resulting directly from dehydration of the ions from droplets in the electrospray process and structures produced by activation and refolding of proteins into additional structures (i.e., CIU), the activation enthalpies, entropies, and free energies for the covalent and proton transfer reactions are valuable for characterizing the kinetics and mechanisms of these reactions versus CIU processes.…”
Section: Resultsmentioning
confidence: 99%
“…10 We have recently used this reagent to probe gas-phase structures of ubiquitin cations formed from aqueous and low-pH methanolic solutions. 12,38 Since it is of interest to differentiate between gas-phase structures resulting directly from dehydration of the ions from droplets in the electrospray process and structures produced by activation and refolding of proteins into additional structures (i.e., CIU), the activation enthalpies, entropies, and free energies for the covalent and proton transfer reactions are valuable for characterizing the kinetics and mechanisms of these reactions versus CIU processes. The ion/ion reaction products of ubiquitin 6 + ions and sulfo-benzoyl-HOAt 1 − ions formed in the trap cell with the application of various collision energies in the transfer cell are shown in Figure 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Instrumental details have been described previously. [29][30][31][32]42 The NanoLockspray source was used with proteins introduced by nanoelectrospray ionization (nESI) from a pulled borosilicate glass capillary (P97 Flaming/Brown Micropipette puller, Sutter Instrument Company, Novato, CA) with a platinum wire inserted through the distal end of the capillary held at a positive potential of ~1 kV. Various charge states of the proteins produced by nESI were mass selected in the quadrupole for reaction with ND3 in the trap cell (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The lack of a solvent system serves to strengthen salt bridges in the gas phase and salt bridges are expected to be the final structural motifs from solution that are lost. 60 ECD 32 and ultraviolet photodissociation (UVPD) 61 have been previously used to assign protonation sites of native-like ubiquitin structures. Notably, both ECD and UVPD showed that lysine 33 is protonated for the 6 + ion, while UVPD and examination of ECD of the undeuterated 5 + ions showed that lysine 33 was not protonated for the 5 + ions, since the charge state of the fragments does not increase between z42 2+ and z45 2+ (i.e., between residues glycine 35 and lysine 29, respectively).…”
Section: Equation (1)mentioning
confidence: 99%
See 1 more Smart Citation